Chlorination and Cleavage of Lignin Structures by Fungal Chloroperoxidases - Ortiz-Bermúdez, Patricia (American Society for Microbiology, 2003)
Two fungal chloroperoxidases (CPOs), the heme enzyme from Caldariomyces fumago and the vanadium enzyme from Curvularia inaequalis, chlorinated 1-(4-ethoxy-3-methoxyphenyl)-2-(2-methoxyphenoxy)-1,3-dihydroxypropane, a dimeric model compound that represents the major nonphenolic structure in lignin. Both enzymes also cleaved this dimer to give 1-chloro-4-ethoxy-3-methoxybenzene and 1,2-dichloro-4-ethoxy-5-methoxybenzene, and they depolymerized a synthetic guaiacyl lignin. Since fungal CPOs occur in soils and the fungi that produce them are common inhabitants of plant debris, CPOs may have roles in the natural production of high-molecular-weight chloroaromatics and in lignin breakdown.